An expanded framework for wildland–urban interfaces and their management. Issue 9 (21st June 2022) - Jenerette, G Darrel; Anderson, Kurt E; Cadenasso, Mary L; Fenn, Mark; Franklin, Janet; Goulden, Michael L; Larios, Loralee; Pincetl, Stephanie; Regan, Helen M; Rey, Sergio J; Santiago, Louis S; Syphard, Alexandra D
Abstract : Wildland–urban interfaces (WUIs), the juxtaposition of highly and minimally developed lands, are an increasingly prominent feature on Earth. WUIs are hotspots of environmental and ecological change that are often priority areas for planning and management. A better understanding of WUI dynamics and their role in the coupling between cities and surrounding wildlands is needed to reduce the risk of environmental hazards, ensure the continued provisioning of ecosystem services, and conserve threatened biodiversity. To fill this need, we propose an expanded framework for WUIs that not only conceptualizes these interfaces as emergent and functional components of socioecological processes but also extends them vertically from the bedrock to the top of the vegetation and horizontally across heterogeneous landscapes. This framework encourages management that reconciles pervasive trade‐offs between development and resulting multiple environmental impacts. Focusing on southern California as a case study, we use the framework to facilitate integration across disciplines and between scientists and managers.